A regiocentric economic sensitivity analysis for scandium recovery from red mud. (2021) - Narayanan, Remya P.; Palantavida, Shajesh; Emmert, Marion H.; Kazantzis, Nikolaos K.
Abstract: Red mud is the industrial waste generated from bauxite processing and is a highly alkaline and hazardous material that has been stockpiled over decades near aluminum mining sites all over the world. The chemical composition of stockpiles depends on the region and is rich in transition metal oxides and metal ions along with rare earth metals. Remediation of red mud is of utmost importance due to the ecological danger they present and also due to the huge quantities produced every day. Even though red mud contains valuable metals, remediation with their extraction is not economically attractive. Recently the authors have developed a process for the recovery of scandium from red mud and optimized it for economic viability using cost evaluation studies. But the amount of Sc depends on the place of generation. Various red mud samples from Jamaica, Alcoa (US), Canada, Korea and India were collected and analyzed using TXRF, XRD, SEM, EDX. A preliminary comparative probabilistic economic assessment of the earlier developed process is done using Monte Carlo simulation Techniques with the red mud samples of various origins.